Sirtuins and mechanisms of diabetic lung damage: a scientific discussion. A review - Sergei L. Babak; Marina V. Gorbunova; Andrey G. Malyavin; Vladislav S. Borovitsky (Consilium Medicum)
Induced tissue damage in target organs (kidneys, heart, eyes, liver, skin, nervous system) significantly contributes to the morbidity and mortality of patients from diabetes mellitus (DM). In recent decades, the question has been actively discussed: should the lungs be regarded as a target organ for diabetes? The c collected data demonstrate histological and functional lung disorders in DM patients. This suggests that the lungs are a target organ for diabetes. It is known that sirtuins regulate a number of physiological processes and affect obesity, insulin resistance, type 2 DM, heart disease and aging. In this review, we have tried to summarize the knowledge about the contribution of sirtuins to cellular regulation and the formation of pulmonary disease in patients with type 2 DM.